Analisis Keterlaksanaan Pembelajaran Berdiferensiasi Ditinjau dari Kesiapan Guru dan Siswa di Kelas X - Muhammad Sobirin (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to analyze the implementation of differentiated learning on sequences and series in Grade X, focusing on the readiness of teachers and students as supporting factors. Differentiated learning is essential to meet the diverse learning needs of students with varied backgrounds and abilities. However, the success of this method heavily depends on teachers' readiness to plan and implement it, as well as students' readiness to participate effectively. This research employs a qualitative method with a case study approach, collecting data through questionnaires and observations at several high schools. The findings indicate that teachers' readiness to apply differentiated learning falls into the moderate category, while students’ readiness varies according to their initial abilities and learning motivation. Although differentiated learning can be applied to sequences and series, there are challenges related to time constraints and supporting resources. In conclusion, the success of differentiated learning on this topic relies significantly on optimal teacher readiness and adequate support for students. This study recommends additional training for teachers and efforts to enhance students’ motivation and engagement in differentiated learning.